2003
DOI: 10.1038/sj.onc.1206444
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma etiology: where are we?

Abstract: Melanoma incidence rates are rising rapidly, particularly in older men. Older men are also more likely to have thick melanomas, which confer high mortality and morbidity. The reasons for the rate of increase are not known; increasing sun and UV exposure, however, is the major hypothesized explanation. In the past several years, two major susceptibility genes for melanoma, CDKN2A and CDK4, have been identified, but the two genes together account for a minority of familial melanoma. Other highrisk susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
1
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(169 citation statements)
references
References 115 publications
8
147
1
11
Order By: Relevance
“…Nevi A major risk factor for melanoma is number and type of nevi. Nevi are benign collections of melanocytes, and the numbers of nevi have been implicated in numerous studies as the most important risk factor for melanoma, with an increased number of nevi associated with an increased risk of disease [15,24,158,230]. A meta-analysis has shown that individuals with more than 100 normal nevi are at an almost seven times greater risk than individuals with few (≤15) nevi [75,76].…”
Section: Host Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevi A major risk factor for melanoma is number and type of nevi. Nevi are benign collections of melanocytes, and the numbers of nevi have been implicated in numerous studies as the most important risk factor for melanoma, with an increased number of nevi associated with an increased risk of disease [15,24,158,230]. A meta-analysis has shown that individuals with more than 100 normal nevi are at an almost seven times greater risk than individuals with few (≤15) nevi [75,76].…”
Section: Host Factorsmentioning
confidence: 99%
“…An inverse relationship has been consistently demonstrated between melanoma risk and degree of skin pigmentation [6,24,159]. Fair-skinned individuals have a much higher risk for developing melanoma than dark-skinned individuals, such that risk estimates in individuals of non-European descent, who are typically darker-skinned, are up to 10-20-fold less than those in individuals of European descent, who are typically lighter-skinned [15,230].…”
Section: Other Pigmentation Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous malignant melanoma (CMM) is an aggressive form of skin cancer with increasing incidence in the Western world (Tucker and Goldstein, 2003). CMM has a heterogeneous and unpredictable clinical course with a potential for aggressive growth and refractoriness to available chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The rising incidence makes this cancer an issue of ever increasing clinical and economic importance and research interest (Garland et al, 2003;Tucker and Goldstein, 2003;Berwick et al, 2005). The identification of new prognostic markers may help to better distinguish low from high-risk disease apart from the classical histopathologic and clinical criteria (Carlson et al, 2005) and may offer new targets for therapy.…”
mentioning
confidence: 99%